Azo-Compound-Mediated Cyanoalkylation of Alkenes by Copper Catalysis: General Access to Cyano-Substituted Oxindoles - Tang, Shi; Zhou, Dong; Li, Zhi-Hao; Fu, Mei-Jun; Jie, Li; Sheng, Rui-Long; Li, Shu-Hua (Synthesis, 2015)
A practical and highly efficient azo-compound-mediated/ promoted radical cyanoalkylation of activated alkenes by copper catalysis was developed, which allowed for general synthesis of oxindoles bearing various nitrile moieties, especially the rarely reported 3° nitrile moiety via cascade radical addition/C(sp2)–H cyclization. This protocol demonstrates that DIAD served for a new promoter instead of usual Ag salts or bases in the C(sp3)–H functionalization of acetonitrile for the first time. The use of readily available AIBN and beyond as the radical sources, and inexpensive copper as the catalyst, as well as the simplicity of operation and handling, make this protocol an attractive access to therapeutically important cyano-substituted oxindoles.
Keywords: azo compounds; cyanoalkylation; alkenes; radical; copper catalysis